A COMPARATIVE ANALYSIS OF CORONARY ADVENTITIAL T-LYMPHOCYTES -AN AUTOPSY STUDY - Zubair, Alia; Mubarik, Azhar; Jamal, Shahid; Naz, Salma (Journal of Ayub Medical College Abbottabad, 2010)
Background: Recent clinical and histopathologic data suggests that inflammation plays a key role in coronary artery plaque instability and subsequent occlusive thrombosis. The intima has received much attention as a site of inflammation, while the adventitia has remained relatively unexplored. The aim of the present study was to investigate the frequency of inflammatory activity in the cap and shoulder region of unruptured, atherosclerotic lesions in coronary arteries and to correlate these findings with distribution of inflammatory cells in adventitia. Methods: The study was carried out in Histopathology Department, Army Medical College, Rawalpindi and National University of Sciences & Technology (NUST), from August 2008 to July 2009. Sixty-seven autopsy cases performed at Military Hospital Rawalpindi, Pakistan were selected. The cases were divided into study group and control group. Case group (n=35) included those where cause of death was ischemic heart disease. Those coronary arteries were taken as control (n=32) where atherosclerotic changes were found by chance (death without history of ischemic heart disease). Plaques in each group were assessed by light microscopy and by immunohistochemistry. Results: The ages of the deceased ranged from 38 to 49 years. Within study group, adventitial lymphocytes exhibited strong correlation with erosion, thrombus formation in culprit plaque (p=0.001). No correlation was found between adventitial T-lymphocytes and erosion of plaque (p=0.700) in control group. In 72% of culprit plaques moderate staining for T-lymphocytes was observed in adventitia as well as intima. In control group, most of the cases contained scattered cells. Few cases of stable plaques revealed lymphocytes as clusters, both in adventitia and in intima. Conclusion: Adventitial inflammation may play a pivotal role for atherosclerotic lesion histology and atheroma instability. With the help of these autopsy findings, we hope to be able to reduce the incidence of culprit plaques related to inflammatory reaction in patients of ischemic heart disease. Keywords: Atherosclerosis, Culprit plaque, Adventitial inflammation, T-lymphocytes